Municipal Leadership of Climate Adaptation Negotiations: Effective Tools and Strategies in Houston and Fort Lauderdale. Issue 1 (January 2017) - Williams, Mark K.; Green, Alex; Kim, Ella
Abstract : Negotiation analysis of climate change–related issues has largely focused on public dispute resolution mechanisms that are typically applied in the face of specific environmental crises, or on multiparty diplomacy relating to international climate agreements. Mayors and other municipal leaders, however, are increasingly taking steps to negotiate urban planning efforts with stakeholders to implement policies for managing the intensifying impact of climate change. In this article, we analyze negotiations in Houston, Texas, and Fort Lauderdale, Florida, to identify which methods municipal leaders employed to conduct negotiations to implement climate adaptation policies and also consider whether those methods were effective. The two cities present two differing city management structures: Houston has a strong mayor‐driven system, while Fort Lauderdale uses a city commission and city manager system. In this article, we examine the barriers that leaders must overcome and consider their options for negotiating lasting agreements.